Stock assessment of the ribbonfish, Trichiurus lepturus Linnaeus, from the Indian waters - Thiagarajan, R; Lazarus, S; Sastry, Y Appanna; Khan, M Zafar; Kasim, H Mohamad; Scarah, K S (Indian Journal of Fisheries, 2011)
The fishery of the ribbonfishes and population of the species Trichiurus lepturus Linnaeus were studied fromthe all-India data collected during 1971-89. The last five years were the most productive with an annual averagecatch of 79 220 tonnes, contributing 4.5% of the total fish catch and exhibiting an increase of about 48% overthe 1970-81 period. This increase in the landings was attributed to the increased exploitation by trawl nets instates like Gujarat and Maharashtra. Trawl net contributed about 50% ofthe total catch. About 75% of the catchcame from the west coast and the rest from the east coast. In the west coast the peak fishing season was in thefourth quarter except in Kerala where it was in the third quarter. In the east coast also, peak season was in thefourth quarter in the northern states and in the third quarter in the southern states. The total instantaneousmortality (Z) rates were estimated as 3.15 and 3.71 for the east and west coasts respectively by length convertedcatch curve method. By Jones' cohort analysis they were estimated at 3.32 for the east and 3.77 for !he westcoasts.